Exergy analysis on steam power plant - Irandegani, Mohammad Yousef (2012)
In this study, the energy and exergy analysis as well as the effect of varying the reference environment temperature on the exergy analysis of an actual steam power plant has been investigated. Simulation methodology of power generation cycle is discussed and it is applied to case study. In the considered power cycle, the maximum energy loss was found in the condenser where 129 MW is lost to the environment in the other hand just 7 MW was lost from the boiler system. The maximum value of the exergy destruction ratio to total exergy destruction was found in the boiler system (77%) next to by the turbine (14%) followed by condenser (9%). In addition, the calculated thermal efficiency based on the lower heating value of fuel was 27% while the exergy efficiency of the power cycle was found 25%. The largest magnitude source of exergy destruction related to the boiler system where chemical reaction is the most important source of exergy destruction in a combustion chamber that may due to the excess air fraction and the temperature of the air at the inlet. The efficiencies of combustion can be increase by preheating the combustion air and reducing the air-fuel ratio. Consequently, the boiler is the major source of irriversibilities in the system, even though, the percent exergy destruction and the exergy efficiency of each component in the system changed with reference environment temperature.